Korelasi Skor Mini Mental State Examination (MMSE) dan Montreal Cognitive Assessment Versi Indonesia (MoCA-Ina) Sebagai Instrumen Evaluasi Fungsi Kognitif pada Pasien Epilepsi di Kota Mataram - Nurfadia, Muhammad Fabian; Harahap, Herpan Syafii; Rizki, Mohammad; Sahidu, Muhammad Ghalvan; Hunaifi, Ilsa (Faculty of Medicine Universitas Mataram, 2021)
Background: Epilepsy is the highest prevalence diseases in neurology. The decreased of cognitive function is one of the complications which is important. The purpose of this study is to determine the correlation between Mini Mental State Examination (MMSE) and Montreal Cognitive Assessment in Indonesian Version (MoCA-Ina) score on patient with epilepsy in Mataram. Method: This is an observational cross-sectional study with 56 subjects with epilepsy from West Nusa Tenggara 2 center hospital. Data that collected from the samples were MMSE and MoCA-Ina score. Beside of that patients’ characteristics data were also collected which is age, gender, education, seizure control, etiology of epilepsy, seizure type, antiepileptic drugs treatment, and smoking status from the subjects. Both instrument’s mean scores were analyzed for the correlation using Spearman correlation test. Result: This study showing that the subjects average age were 32.9 years old, female (55.4%), and low educated (62.5%). According to the clinical characteristics most subjects were not-depressed (67%), poor quality-controlled seizure (55.4%), idiopathic etiology (66.9%), generalized seizure (71.4%), and having monotherapy (85.7%). Most of the subjects were not a smoker (76.8%). In this study both the mean score of MMSE and MoCA-Ina were 25.3 and 21.3. MMSE and MoCA-Ina score mean have a strong correlation (r=0.766; p<0.001). Conclusion: MMSE and MoCA-Ina score mean on patients with epilepsy have a strong correlation. Therefore, both instruments could be used to evaluate cognitive function on patients with epilepsy